Pacientes hospitalizados por pneumonia adquirida na comunidade apresentam redução da capacidade funcional, força muscular periférica e qualidade de vida - José, Anderson (2011)
The reduction in the functional capacity (FC) and peripheral muscle strength (PMS) demonstrated in patients with COPD during hospitalization has not been studied in patients hospitalized with community-acquired pneumonia (CAP). We aimed to evaluate the FC in patients hospitalized for CAP and correlate it with pulmonary function, PMS, quality of life (QoL), dyspnea and length of hospital stay. Methods: We prospectively evaluated 45 patients (49 ± 16 years, FEV1: 57.8 ± 17.8% of predicted; CAP Group) and 20 healthy subjects (53 ± 17 years; Control Group). They were randomized to perform, on separate days, the 6-minute walk (6MWT), measurements of PMS, Glittre test (GT) and the Chester step test (CST). Additionally the SF36 questionnaire and the MRC scale were evaluated. There were significant differences between groups (CAP and Control) for 6MWT (381.3 ± 108 m vs 587.1 ± 86.8 m), GT (272.8 ± 104.3 vs 174 ± 39 sec), CST (73.2 ± 61.8 vs 149.2 ± 65.9 steps). The CAP Group also presented with worse QoL scores, reduced strength (quadriceps, hamstrings and biceps) and higher scores of dyspnoea. Significant correlations were observed between 6MWT and GT (r = -0.66), CST (r = 0.49), FC domain of SF36 (r = 0.43) and PMS. The time spent to perform GT correlated with the length of hospital stay (r = 0.35; p = 0.02) Conclusion: Patients with CAP presented with reduced FC, PMS and QoL during hospitalization. The 6MWT correlated with the PMS, QoL and other FC tests.